Conflict in hellas - Materials for an Integration of the Greek Spirit (Paper read to Architectural Student's Society) - Martienssen, Rex D (Transvaal, Natal and Orange Free State Provincial Institutes of South African Architects and the Chapter of South African Quantity Surveyors, 1935)
When we build, we establish a relationship more or less satisfactory between the volume of the building and the greater volume which encloses it. The enveloping elements of the building-form provide the transition, and it is in this actual transition that the degree of strength and the kind of relationship is established.
Keywords: Martienssen, Rex D; Greek Spirit; Delphi; Hellas